Determinants of customer switching behaviour: evidence from the non-bank financial institutions in Ghana. (2017) - Tweneboah-Koduah, Ernest Yaw; Mann, Victoria; Quaye, Daniel Marboye
Due to the intensified competition in the financial sector as a result of homogenous products and services, it is becoming increasingly important for service providers to take steps to retain their customers. The paper sought to investigate the factors influencing NBFIs' customer switching behaviour. Data collected from 400 respondents was analysed using descriptive statistics and multiple regressions. The study found excessive pricing, poor service quality, customer dissatisfaction and lack of trust to have a statistically significant influence on NBFIs' customer switching behaviour in Ghana.